A structurally simple donor with a low recombination rate for high-performance dye-sensitized solar cells. (June 2019) - An, Jincheng; Yang, Xichuan; Wang, Weihan; Zhang, Li; Cai, Bin; Wang, Haoxin; Wang, Xiuna
Graphical abstract: Highlights: A structurally simple donor is used to synthesize new dyes. The relationship between structure and the photovoltaic performance of the DSC. The different open voltages of two dyes are explained by EIS. Abstract: Two dyes with dithieno[3, 2-b:20, 30-d] pyrrole (DTP) as the donor (An101 andAn102 ) have been synthesized and characterized.An101 andAn102 were applied to dye-sensitized solar cells (DSSCs) and power conversion efficiencies (PCEs) of 8.0% and 9.5% were achieved with the I 2− /I 3− redox couple, which correspond to open voltages ( V oc ) of 784 and 690 mV, current densities ( J sc ) of 15.1 and 20.0 mA cm −2, the fill factors of 67.2% and 68.7%, respectively, under AM1.5G irradiation. It is worth noting that the different connection locations of the donors with the π-bridge result in different PCEs.An102 has a higher J sc owing to its high molar extinction coefficient and small torsion angle, which increase the light-harvesting ability and coplanarity.An101 has a higher V oc owing to introduction of the alkoxybenzene group, which can effectively suppress recombination with the electrolyte and dye. By scanning with different bias voltages with electrochemical impedance spectroscopy, the reason for the high voltage of theAn101 dye is up-shift of the TiO2 conduction-band edge and elongated electron lifetimes. However, the main reason for the relatively high PCE of theAn102 dye is the coplanarity, which results in good long-term stability.